2015
DOI: 10.1007/s11295-015-0911-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate genes associated with mealiness and maturity date in peach [Prunus persica (L.) Batsch] using QTL analysis and deep sequencing

Abstract: Artículo de publicación ISIPeach and nectarine quality traits such as flavor, texture, and juiciness are important for consumer acceptance. Maturity date (MD) also plays a role in the fruit-ripening process and is an important factor for marketing fresh fruit. On the other hand, cold storage produces a physiological disorder known as chilling injury where the most important symptom is a lack of juice in the flesh or mealiness (M). In this study, we analyzed an F2 population obtained from a self-pollination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 74 publications
10
82
0
Order By: Relevance
“…To our knowledge, this is the sixth full map produced with the 'IPSC 9K peach SNP array v1' in peach, although others have been constructed with this array technology in other Prunus-derived progenies Yang et al 2013;Martínez-García et al 2013a;Frett et al 2014;Pacheco et al 2014;Romeu et al 2014;Da Silva-Linge et al 2015;Nuñez-Lillo et al 2015). The length of genetic linkage maps mostly based on SNP markers were more saturated compared with the previously published maps, with the exception of the T × E Prunus reference map (Dirlewanger et al 2006).…”
Section: Genetic Mapsmentioning
confidence: 86%
See 2 more Smart Citations
“…To our knowledge, this is the sixth full map produced with the 'IPSC 9K peach SNP array v1' in peach, although others have been constructed with this array technology in other Prunus-derived progenies Yang et al 2013;Martínez-García et al 2013a;Frett et al 2014;Pacheco et al 2014;Romeu et al 2014;Da Silva-Linge et al 2015;Nuñez-Lillo et al 2015). The length of genetic linkage maps mostly based on SNP markers were more saturated compared with the previously published maps, with the exception of the T × E Prunus reference map (Dirlewanger et al 2006).…”
Section: Genetic Mapsmentioning
confidence: 86%
“…Moreover, Sánchez et al (2014) found that chromosomes 2, 1, and 3 were missing in a pseudo-test cross population between the cultivars 'MxR_01' and 'Granada'. The lack of polymorphic SNPs in certain chromosomes is caused by homozygosis in the peach genome and is probably due to germplasm background Sánchez et al 2014;Nuñez-Lillo et al 2015). Verde et al (2012) Table 3).…”
Section: Genetic Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…NACs constitute one of the largest plant TF families and are key regulators of developmental programmes and stress response ). In addition, more recently, Nuñez-Lillo et al (2015) have found a QTL in the same region of LG 4 of peach linked to maturity date, explaining around 80 % of the variability.…”
Section: Genetic Linkage Analysis and Qtl Identificationmentioning
confidence: 98%
“…Another important fruit quality trait is resistance to cold storage, slow ripening (SR) is an interesting trait for selecting this resistance. Whole genome analysis allowed the identification of a deletion co-localizing with the SR trait (Nuñez-Lillo et al, 2015). Fruit acidity is a major determinant of fruit quality in peach.…”
Section: Impact Of Ngs On Breedingmentioning
confidence: 99%